Remaja Anti Anemia (RANIA) Sebagai Upaya Pencegahan Stunting Pada Remaja Putri Di Madrasah Aliyah Ushuluddin Singkawang - Nasla, U. Evi; Valentina, Febi Rizki; Welliana, Willi; Selisari; Ramadanti, Fitri (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2025)
Stunting is a serious health issue, particularly among children under five years old. This condition arises due to prolonged nutritional deficiencies and is often influenced by factors such as recurrent infections and an unbalanced diet, characterized by a height that is significantly lower than the growth standard. The prevalence of stunting in Indonesia decreased to 21.6% in 2022, down from 24.4% in 2021. However, in Singkawang City, the prevalence of stunting among children under five increased from 21.2% in 2021 to 23.5% in 2022. Preventing stunting is a national priority in Indonesia to ensure the younger generation can grow and develop optimally, both physically and cognitively. One key strategy for accelerating stunting reduction is addressing issues among adolescents. Anemia is one of the most common nutritional problems faced by adolescents. Adolescent girls with anemia are at risk of becoming anemic pregnant women, which increases the likelihood of giving birth to low birth weight babies and stunting. The purpose of this community service program is to improve adolescent girls' knowledge about anemia. The methods used in this program include education through lectures, discussions, Q&A sessions, and hemoglobin level examinations. The partner for this activity was Madrasah Aliyah Ushuluddin Singkawang. The results of this program showed that 56% of adolescents experienced anemia, and there was an improvement in their knowledge about anemia, as indicated by a 21.3-point increase in the average pre-test and post-test scores.